Sleep Quality and Self-Harm Tendencies among Final-Year Students - Nurtiningtyas, Vivi; Oktaviana, Wita (Jurnal Keperawatan Profesional (KEPO), 2025)
Poor sleep quality cloud disrupt the sleep-wake rhythm, particularly affecting brain function and potentially leading to various health problems. The impact of inadequate sleep encompasses both physiological and psychological disturbances, including fatigue, physical weakness, reduced physical activity, and weakened immune function. This study aimed to raise awareness among students, particularly in academic settings, about the importance of maintaining high-quality sleep in support of their mental health. The research employed a descriptive quantitative design using a questionnaire-based survey, with a random sampling technique. The frequency distribution results showed that 21,5% of subjects exhibited healthy sleep patterns, while the remaining 78,5% were categorized as having suboptimal sleep patterns. Self-harm tendencies were divided into three categories: no self-harm (92,5%), mild self-harm (5,4%), and severe self-harm (2,2%). Correlation analysis using the Spearman rank test indicated a significant positive relationship between sleep quality and self-harm tendencies (r = 0,353; p-value = 0,001). Therefore, final-year students working on their theses are advised to manage their time more effectively and pay attention to both the duration and quality of their sleep as a preventive measure against sleep disturbances. An imbalanced sleep pattern can trigger negative emotional responses and reduce an individual’s ability to regulate emotions.